Estimation of β-sitosterol as a tool to detect ghee adulteration with palm oil - B G, Shilpashree (Indian Journal of Dairy Science, 2024)
Ghee is a popular dairy product in India and most expensive fat in India so it is prone to adulteration with highly manipulated inexpensive oils/fats, especially during the lean season. Dry fractionation is the most cost-effective method of modifying the physical properties of milk fat. β-sitosterol is a principal sterol in edible oil (palm oil). The use of chromatography to separate sterols from ghee fractions could be a novel way to distinguish between β-sitosterol and cholesterol. In the current study, ghee was added with palm oil at levels of 0, 5, 10, and 20%. β-sitosterol was estimated qualitatively using the reverse phase-thin layer chromatography method (RP-TLC) and found better spot in liquid fraction than control ghee even at a 5 % level. This result was quantified using RP-HPLC and shows L20 with palm oil (5%) 0.1755 ppm concentration, S20 with palm oil (5%) 0.0755 ppm concentration.